A study of the genus Semnostola Diakonoff from China with the description of a new species (Lepidoptera: Tortricidae: Olethreutinae) - Xu, Zhang; Wang, Shuxia (Zootaxa, 2006)
We report five species of Semnostola from China, including one new species, S. grandaedeaga, sp. nov., and one newly recorded species, S. triangulata Nasu & Kogi. The generic characters are amended based on the description of the new species. Photographs of the adults and the genitalia are provided. A key for the identification of the world species of Semnostola is given.